2009
DOI: 10.1007/s00423-009-0468-x
|View full text |Cite
|
Sign up to set email alerts
|

Open versus endovascular repair of acute aortic transections—a non-randomized single-center analysis

Abstract: Endovascular treatment of acute aortic transections is associated with a reduced perioperative mortality compared to conventional surgery with no difference regarding midterm survival. Long-term data are still required to define the definite role of TEVAR in TAT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…The median preoperative hemoglobin level was 9.9 (range, [6][7][8][9][10][11][12][13][14] and 30% of our patients showed a positive shock index. In total, six patients were considered as hemodynamic unstable, receiving preoperative inotropes and volume therapy with blood transfusion.…”
Section: Patient Populationmentioning
confidence: 69%
See 2 more Smart Citations
“…The median preoperative hemoglobin level was 9.9 (range, [6][7][8][9][10][11][12][13][14] and 30% of our patients showed a positive shock index. In total, six patients were considered as hemodynamic unstable, receiving preoperative inotropes and volume therapy with blood transfusion.…”
Section: Patient Populationmentioning
confidence: 69%
“…Especially the large proportion of patients with traumatic transection (15%-68%) in these studies, which have been excluded in our analysis, warrants consideration as these patients are usually young, "healthy" trauma victims and show favorable mortality and morbidity rates after TEVAR as proved in various single center series and meta analysis. [8][9][10] In opposition to that, this series represents a rather old (median age, 75 years), highly comorbid (83% patients with coronary heart disease, 43% patients with renal insufficiency, and 30% patients with COPD) patient cohort, resulting in high cardio-pulmonary and renal complications with consecutive perioperative death. Midterm survival is influenced by these parameters.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The mortality rate in the open repair group needs to be analyzed closely, however. Most other reviews have reported much higher mortality rates ranging from 18 to 50 per cent, [21][22][23][24] although one report with over 50 patients in the open group listed mortality as low as 8 per cent. 25 In a recent study similar to ours comparing TEVAR and open repair, 36 per cent of the patients undergoing open repair died in the hospital versus only 14 per cent in the TEVAR group.…”
Section: Discussionmentioning
confidence: 99%
“…A major morbidity postsurgical repair is paraplegia which occurs at a rate of about 19.2% and is usually the result of spinal ischemia. Based on multiple published retrospective analyses comparing open surgical repair to endovascular repair for TAI, surgeons now prefer endovascular management of TAI. In fact, the Society for Vascular Surgery recommends endovascular management for TAI and it is becoming the preferred treatment of TAI at most centers.…”
Section: Discussionmentioning
confidence: 99%